History of biohumus and its importance in soil fertility (Texas Journal of Agriculture and Biological Sciences, 2024)
In the article, a detailed introduction to the promising direction in the field of increasing soil fertility, a real life ointment for the soil, the history of biohumus and its importance in soil fertility and ways of its implementation, the number of nests and the area where they are placed, the number of nests on the preparation and production technology of the California red earthworm and knowing the approximate amount of worms in them, after calculating the required amount of nutrients, bringing it to the specified area and placing it according to the preparation method, high-quality biohumus was obtained